2016
DOI: 10.1097/mcp.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics and interstitial lung disease

Abstract: Purpose of review Interstitial lung disease (ILD) is comprised of a heterogeneous group of disorders with highly variable natural histories and response to therapies. Pharmacogenetics focuses on the variability in drug response due to the presence of genetic factors that influence drug metabolism or disease activity. In this article, we review relevant drug-specific and disease-specific polymorphisms that may influence therapeutic response, and then highlight a recently identified drug-gene interaction in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Are there sex-specific pharmacogenetic differences modifying the effect of antifibrotic drugs? [85].…”
Section: Geneticsmentioning
confidence: 99%
“…Are there sex-specific pharmacogenetic differences modifying the effect of antifibrotic drugs? [85].…”
Section: Geneticsmentioning
confidence: 99%
“…This differentiation is important in the treatment of ILD, because anti-inflammatory medications (i.e. corticosteroids) are currently used in ILD related to collagen vascular disease in contrary to the antifibrotics pirfenidone (Roche, Basel, Switzerland) and nintedanib (Boehringer Ingelheim, Ingelheim am Rhein, Germany), which are indicated in patients with idiopathic pulmonary fibrosis (IPF) [7,8]. Thin-slices MDCT is also limited by poor reproducibility of visual scores for ILD abnormalities and lack of specific outcome measures to evaluate response to treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of antifibrotic treatments into clinical practice, which have transformed our understanding of IPF, some patients have remained stable for many years, while others have experienced steady progression, and a minority have experienced rapid disease worsening. Consequently, in recent years, various biomarkers associated with the intricate cellular, biological and immunobiological pathways have been studied as potential indicators of treatment efficacy [37][38][39].…”
Section: Efficacy Of Antifibrotic Agentsmentioning
confidence: 99%
“…DNA samples from patients enrolled in the Anti-Coagulant Effectiveness in Idiopathic Pulmonary Fibrosis trial were used in a genome-wide association study [63]. Examination of this group revealed a possible association between warfarin treatment and the MUC5B promoter polymorphism, although the sample size was insufficient for formal interaction testing [39]. Notably, among the genotyped study participants, a greater number of deaths were observed in individuals with the polymorphism who received warfarin compared to those who received placebo (6 on warfarin vs. 1 on placebo), suggesting a possible interaction.…”
Section: Safety Of Antifibrotic Agentsmentioning
confidence: 99%
See 1 more Smart Citation